Influence of molecular weight of chitosan on the microstructures and photocatalytic property of ZrO2 prepared by chitosan templates method. (November 2016) - Wu, Taiheng; Shao, Qian; Ge, Shengsong; Zhao, Wenli; Liu, Qingyun
Graphical abstract: Highlights: ⿢ ZrO2 particles have been fabricated with degraded chitosan as template. ⿢ ZrO2 particles morphologies changed along with different molecular weight chitosan. ⿢ Different molecular weight chitosan obtained by microwave hydrothermal method. ⿢ ZrO2 with lower molecular weight chitosan showed higher photocatalytic activity. Abstract: ZrO2 particles with different microstructure have been fabricated through an easy method with chitosan of different molecular weights as template. The chitosan of different molecular weights was obtained through synergistic degradation of raw chitosan by α-amylase and H2 O2 using microwave hydrothermal method in low concentration acetic acid (1% V / V ). The as-synthesized ZrO2 particles were characterized by wide-angle powder X-ray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy, and N2 adsorption⿿desorption. The possible formation mechanism of ZrO2 particles with different microstructure has been proposed, and the photocatalytic activity of the as-synthesized products was assessed by monitoring the photodegradation of Rhodamine B (Rh B) under UV irradiation. Morphologies of as-synthesized ZrO2 particles changed significantly with the different molecular weight of chitosan. As the molecular weight of chitosan decreased, the morphologies of as-synthesized ZrO2 particles showed aggregate, nano-cubes, and nano-sheets, respectively. The ZrO2 particles prepared with lower molecular weight chitosan as the template showed higher photocatalytic activity. The degradation efficiency of ZrO2 with 3.1 ÿ 10 7 and 2.4 ÿ 10 4 Da chitosan as template was 64.4% and 86.2%, respectively.